PERENCANAAN PENGOLAHAN AIR LIMBAH SISTEM TERPUSAT (STUDI KASUS DI PERUMAHAN PT. PERTAMINA UNIT PELAYANAN III PLAJU – SUMATERA SELATAN) - Puji Retno Wulandari (Jurnal Teknik Sipil dan Lingkungan, 2014)
The level of pollution is the same comparable to the rate of population growth in the region. The more densely populated an area, the potential of the damaged environment will be even greater. This addition led to increased quantity and quality of wastewater generated, so the installation of better waste water treatment is necessary because the current management isn’t up to standard. To reduce the impact of pollution, a plan to build a wastewater treatment facilities in the domestic communal housing of PT. Pertamina UP III Plaju is like Wastewater Treatment Plant (WWTP).This study aims to calculate (1) the next 10 years population projection, (2) the total volume of waste water generated, (3) the dimensions of the channel carrier and wells collector, and (4) the dimensions planned of the IPAL unit and its area of ​​land required for construction of the plant. The methods used for collecting the data are field surveys, documentation and review of the literature relating to the subject matter. The results of the calculation of wastewater discharge to the next 10 years is equal to 6.574 L / sec. Pipes used as main pipe is a kind of PVC pipe with a diameter of 216mm (8 ") with the roughness Manning coefficient of 0.009. Based on the selection criteria for the wastewater treatment process in accordance with the conditions of the location, the time for planning is to be used with aerobic – anaerobic waste water biofilter. The dimensions of the main processing of waste water building is 8 meters wide with a depth of 2 m below the ground surface and 1.5 m above the ground. The length of the initial settling basin is 15 m, 14 m anaerobic biofilter tank, 12 m aerobic biofilter tank, and 15 m final settling basin. Equalization tank made ​​into 2 tanks with each 10 m wide and 16 m long.The ​​land required to build the installation is approximately 70 m x 20 m square. Key Words : domestic wastewater, wastewater treatment, aerobic - anaerobic biofilter